2021
DOI: 10.3390/pr9030404
|View full text |Cite
|
Sign up to set email alerts
|

Improving Low Rank Coal Flotation Using a Mixture of Oleic Acid and Dodecane as Collector: A New Perspective on Synergetic Effect

Abstract: The mixed collector can improve low rank coal flotation efficiency, but its synergistic mechanism needs to be further explored. In this paper, oleic acid-dodecane (OA–D), oleic acid (OA), and dodecane (D) were employed to treat the low rank coal for revealing new synergistic mechanism of the mixed collector. First the surface free energy of the coal, the surface free energy of coal–water and coal–water–coal were calculated. Then wetting heat measurement, X-Ray Photoelectron Spectroscopy (XPS) and FTIR were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The effect of OA–D on LRC surface hydrophobicity improved the adhesion strength and stability between bubbles and the LRC surface so as to reduce the particle detachment probability and increase the flotation recovery. This has been confirmed in our previous flotation test, , in which the best flotation result was obtained using OA–D as the collector at the dosage of 3 kg/t, and the combustible matter recovery was 25.77 and 48.86% higher than that of OA and D, respectively. Therefore, the results of detachment force and energy measurements in this study are consistent with those of hydrophobicity measurement and flotation test.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The effect of OA–D on LRC surface hydrophobicity improved the adhesion strength and stability between bubbles and the LRC surface so as to reduce the particle detachment probability and increase the flotation recovery. This has been confirmed in our previous flotation test, , in which the best flotation result was obtained using OA–D as the collector at the dosage of 3 kg/t, and the combustible matter recovery was 25.77 and 48.86% higher than that of OA and D, respectively. Therefore, the results of detachment force and energy measurements in this study are consistent with those of hydrophobicity measurement and flotation test.…”
Section: Results and Discussionsupporting
confidence: 83%
“…Thus, the water molecules were accelerated to leave the LRC surface, which increased the lipophilicity and hydrophobicity of the LRC surface. 10 A new synergistic mechanism of oleic acid–dodecane (OA–D) mixed collectors was proposed by An et al 11 On a relatively ordered “supramolecular structure” on the LRC surface, especially, there were hydrophobic and van der Waals forces between the OA chain and the D chain that can promote the formation of a continuous collector film. Although enhancing LRC flotation using a mixed collector has been widely studied, its effect on the bubble–particle detachment process is less-studied, especially the energy feature during the detachment process.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars focus on the new high-efficiency collectors, mainly focusing on the research of polar collectors and compound collectors. The results show that the polar collector can cover the oxygen-containing sites on the surface of LRC and improve the surface hydrophobicity of LRC, so the clean coal yield of flotation is improved. In addition, the synergistic effect of polar and nonpolar components in the compound collector further strengthens the flotation.…”
Section: Introductionmentioning
confidence: 97%
“…Xie et al (2018) investigated the adsorption mechanism of fatty acids with different carbon chain lengths on the surface of fluorapatite based on DFT, and the results showed that fatty acids were chemisorbed on the mineral surface. An et al (2021) found that the essence of synergetic mechanism of oleic acid-dodecane was that they formed a relatively ordered "supramolecular structure" on the low rank coal surface. Foucaud et al (2021b) indicated through DFT calculation that during the hydration process of scheelite, Ca 2+ ions on the mineral surface can adsorb water molecules.…”
Section: Introductionmentioning
confidence: 99%